Mathematical Concepts In The Implementation of Tawaf According to The Quran - Hikmah Suciani; Rosyidi, Muhib (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The Koran covers mathematics in detail, especially multiplication and calculating numbers in various situations and circumstances. Mathematics as the queen of science has an important role as a means of translating concepts in science. so science and mathematics are interconnected and related. Science and mathematics are connected to the verses of the Qur'an. The verses in the Qur'an as the source of everything include technology, science, economics and provide the meaning that all branches of knowledge can be sought for truth from their source in the Qur'an. The method used in this journal uses qualitative research methods with the type of research being literature study. An example of a mathematical concept that has a correlation with the source of the Al-Qur'an is regarding the mathematical concept in the implementation of tawaf, namely when the congregation circles the Kaaba to form a flat circular shape. Keywords: Circle, hajj, phi, tawaf